PERANCANGAN APLIKASI RESERVASI PADA AVRIL NAILZ BERBASIS WEB - stephanie Wijaya; Bagus Mulyawan; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The fast-growing beauty business in Indonesia has made nail art a popular business, especially among women who want to look more attractive. Avril Nailz is a business that provides various nail care and beauty services, ranging from nail care to nail art with various designs and levels of difficulty. Currently, Avril Nailz does not have an adequate reservation system to help manage digital orders and provide complete information needed by customers. Reservation activities are still carried out via WhatsApp, resulting in difficulties in tracking reservations. Therefore, a web-based application is needed to assist Avril Nailz in facilitating reservation activities as well as being a source of information and promotional media. The method used is the Agile Scrum method. Through this application, it is hoped that it can make it easier for customers to make service reservations, provide the information customers need, and assist the owner in tracking bookings.